PENERAPAN MANAJEMEN BERKELANJUTAN UNTUK PERTUMBUHAN PERUSAHAAN - Miftahul Jannah; Hendra Riofita (Lembaga Pengembangan Kinerja Dosen, 2024)
Human Resource Management (HRM) is one of the critical aspects in the success of an organization. In the era of globalization and dynamic changes in various sectors, it is important for companies to develop HR management strategies that not only focus on current needs but are also able to answer future challenges. One approach that is increasingly getting attention is Sustainable Human Resource Management. A literature review will provide an overview of the development of a particular topic. A literature review will allow a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and relevance in the field / to a research result. The results of the study stated that in the era of globalization and digitalization, companies face increasingly complex challenges, ranging from climate change to technological disruption. To face these challenges, the concept of sustainable management is important as a primary strategy in ensuring consistent company growth. Sustainable management not only focuses on short-term profits, but also on the balance between economic, social, and environmental desires. This approach allows companies to create sustainable value for all stakeholders, including shareholders, employees, consumers, and the wider community